(untitled) (Revista Espinhaço, 2013)
The Jequitinhonha High River Valley Archaeological Project (PAAJ) is developed by researchers at LAEP / UFVJM with a main objective to conduct archaeological investigations in a wide area in the River Valley Jequitinhonha, especially the high Valley, a vast area of the Minas Gerais state territory that lacked with academic research. The Serra Negra Archaeological Area is located on the east side of the Espinhaço Ridge, Minas Gerais, between the Jequitinhonha and Doce rivers basins. It is consisted of 65 archaeological sites divided into three archaeological complexes. All are rock shelters (in quartzite), mostly with the presence of rock art, deployed in different biomes that constitute the area. This article aims to present the main features of the archaeological area and to discuss about issues related with the implantation of the archaeological sites in the landscape, geoenvironmental features, and cultural repertoire. As theoretical referential, it was discussed about the landscape archeology, mainly based on persistent places concept. Therefore, it was necessary to adopt a multidisciplinary approach based on research, using various methods and techniques by different Sciences applied to Archaeology. As a result it is expected a more assertive responses about the regional settlement system as well as highlight the main features of the cultural repertoire.